Formação de CEOs para a sustentabilidade: o papel das escolas de negócio - Carreira, Fernanda Cassab (2018)
When we ask CEOs about the sustainability business case, most answers revolve around expressions such as competitive advantage, business opportunity, cost reduction, risk management, and alignment on purpose. In these cases, it is recognized that education for sustainability came about in a little structured way, more with the practice and with space for development. However, from the interviews conducted for this work, it can be seen that not all CEOs can connect sustainability to the core business of the company. But where and how could they graduate for sustainability? The present work sought to understand if there is and, if so, what is the role of Business Schools in the formation of CEOs for sustainability, in order to identify insights for FGV EAESP to advance in this type of education. The literature review sought to (i) understand the conflict between traditional executive education and sustainability, and (ii) to analyze the supply of what exists today in CEOs executive education for sustainability. Empirical research has sought to create, using Grounded Theory, a theory based on the CEO voice of what the role of Business Schools in C-Level education for sustainability will be. The results of the study indicate that Business Schools play a key role in educating managers for sustainability, especially in the early stages of their careers, and that institutions that advance in this direction will be in a competitive advantage due to the low supply of courses in this line. As for education for sustainability for CEOs, space exists, as long as the Schools offer a format that is appropriate to the professional reality of the C-Level. Finally, this work contributes to schools rethinking their teaching-learning approach. Using the mirror as a metaphor, if business schools were created as a reflection of the advancement of the business sector, the transformations that business is going through should be reflected in the teaching and education of managers by the Schools.